Circuit quantum electrodynamics of granular aluminum resonators - N. Maleeva (Nature Portfolio, 2018)
The electrodynamics of superconducting devices make them suitable for applications as detectors, amplifiers, and qubits. Here the authors show that resonators made from granular aluminum, which naturally realizes a network of Josephson junctions, have practically useful impedances and nonlinearities.